The subdomain structure of human serum albumin in solution under different pH conditions studied by small angle X-ray scattering - Olivieri, J. R. [UNESP]; Craievich, A. F. [UNESP] (Springer, 1995)
Small-angle X-ray scattering (SAXS) was used to study structural characteristics of human serum albumin (HSA) in solution under different pH conditions. Guinier analysis of SAXS results yielded values of the molecular radius of gyration ranging from 26.7 Å to 34.5 Å for pH varying from 2.5 to 7.0. This suggests the existence of significant differences in the overall shape of the molecule at different pH. Molecular models based on subdomains with different spatial configurations were proposed. The distance distribution functions associated with these models were calculated and compared with those determined from the experimental SAXS intensity functions. The conclusion of this SAXS study is that the arrangement of molecular subdomains is clearly pH dependent; the molecule adopting more or less compact configuration for different pH conditions. The conclusions of this systematic study on the modification in molecular shape of HSA as a response to pH changes is consistent with those of previous investigations performed for particular pH conditions.
Keywords: Human serum albumin; Molacular configuration; SAXS; Albumin; Ph; Protein structure; Radiation scattering; Chemistry, Physical; Human; Hydrogen-Ion Concentration; Protein Conformation; Scattering, Radiation; Serum Albumin; Solutions; Support, Non-U.S. Gov't; X-Rays